(untitled) (Historia, 2021)
On 10 February 2008, the University of Pretoria (UP) celebrated its centenary. As part of the celebrations, Professor Van der Watt, a retired senior academic and the editor of the fourth volume (1993-2000) of the Ad Destinatum series on the history of the university, as well as the author of Rectores Magnifici (2003), the history of the first eleven university principals, was commissioned to write a history of the institution. He was supported in this endeavour by Professor Karin Harris, director of the UP archive and her efficient staff of archivists.